Pemaknaan Istilah Les Changements Climatiques dalam Accord de Paris dan Penerjemahannya dalam Bahasa Indonesia Persetujuan Paris - Anastasia Pudjitriherwanti; Bernadus Wahyudi Joko Santoso; Siti Ayu Masthuroh (Universitas Negeri Semarang, 2025)
The Paris Agreement is an international accord that aims to limit the rise in global temperature and reduce greenhouse gas emissions. The term les changements climatiques is a key concept that appears repeatedly in the Paris Agreement (2015). In the official Indonesian translation (Persetujuan Paris), this term is rendered as perubahan iklim (“climate change”). This topic is of particular interest because the term is not only scientific in nature but also carries strong political, policy-related, and ideological dimensions. Therefore, its analysis can be approached from three domains: linguistic-ecological, political, and socio-cultural. The occurrence of the term les changements climatiques in the French text, especially in the preamble and in sections acknowledging threats, obligations, and vulnerabilities, is significant. In the Indonesian translation, the term is consistently rendered as perubahan iklim. Based on the data collected, the term appears predominantly in the policy context, referring to state responsibilities, obligations under the convention, and related matters. It also appears in the ecological context, addressing threats to the environment and scientific urgency. Its presence in the socio-cultural category is also evident, although less frequent compared to the other two domains.